Catering for Student Diversity: Building Academic Skills in Graduate Attributes Learning and Assessment Opportunities through Collaborative Work - Owen, Susanne; Davis, Gary (Journal of University Teaching and Learning Practice, 2011)
Australian higher education institutions are increasingly operating within broader political, economic and social frameworks and the global context. The link between productivity and high level skills and qualifications and the importance of establishing a systematic process for ensuring increased participation of those from under-represented groups have been emphasised. In relation to the law profession in Australia, over the past twenty years there has been a proliferation of law schools established to meet increasing demand, with higher student numbers and greater diversity of backgrounds evident. Concerns about the stresses on law students and the consequences for their mental well-being (especially compared to students in other disciplines) have come to the fore following recent research into the issue. In 2007, funding was provided to the Council of Australian Law Deans (CALD) to establish a national exploration of approaches to and the practices of legal education, with the aim of ensuring the provision of high quality outcomes for the increasingly diverse range of legal education students. A key focus was building legal academic skills in using scaffolded learning approaches through establishing collaborative workshops. Surveys, baseline data analysis and network meetings were some of the other methodological processes utilised in the project.The collaborative workshop processes occurring at a national level, resulted in the development of quality assessment tasks in areas such as group work and reflection, with positive written feedback being obtained. This paper focuses on the links between wider assessment approaches within graduate attributes and catering for student diversity.Relevance for redefining effective academic practice within other professional disciplines in the changing contexts of higher education is evident.